Wireless technology: current status and future directions - Khalifa, Othman Omran; Khan, Sheroz; Albagul, A.; Elshabani, M. S. (2006)
Wireless Technology is expected to be the dominant mode of access technology in the future. Besides voice, a new data range of services such as multimedia and high speed data are being offered for delivery over wireless network. Mobility will be seamless, realizing the concept of persons' being in contact anywhere, at any time. Throughout this paper, we review the long, interesting development of wireless communication in the past, examine the current progress in standards and technologies, and finally discuss possible trends for wireless communication solutions.